“Melukis Pantai” Movie as a means for developing student personality in listening subject based on the dimensions of the Pancasila student profile - Aida Azizah; Evi Chamalah; I Kadek Purnawan (BAHASTRA, 2024)
Personality is an individual characteristic that contains individual character education values. The urgency of the research is to reduce the occurrence of moral degradation and answer that films can be a means of providing stimulus for the value of character education. This research aims to determine the results of the analysis of character education values ​​in the film “Melukis Pantai”, the correlation of character education values ​​as a means of developing studentsnta personalities based on the Pancasila student profile, and the development of students' personalities in one of the value analysis subjects. The research method used is qualitative with literature study and a case study approach (direct interview observation). The film “Melukis Pantai” is the data source. Technical data analysis is carried out by collecting, reducing, presenting, and drawing conclusions. The research results show that there are 5-character education values ​​contained in the film “Melukis Pantai”: Curiosity, Hard Work, Creativity, Love of Reading, and Social Concern. There is a correlation between the 5-character education values ​​obtained as a means of personality development. It is also known that the development of students' personalities in listening subjects is based on the results of analysis of character education values ​​in the beach painting film. Through the activity of listening to beach painting films in the Listening course, it can be a means of knowing and developing a personality that is in accordance with the scope of the dimensions of the Pancasila student profile.